The impact of using phase-shift transformers on transmission lines - Ayman Y. Al-Rawashdeh; Abdallah R. Alzyoud; Khalaf Y. Alzyoud; Jawdat S. Alkasassbeh; Ashraf Samara (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Phase shift transformers (PST) are a special type of transformers used to regulate active and reactive power on 3-phase transmission networks by adjusting the difference of voltage phase angle between system nodes. Problems related to power flow and stability, particularly voltage stability issues, are important at the extra high voltage (EHV) and ultra high voltage (UHV) levels due to their extreme sensitivity to active and reactive power changes. Several studies investigated these problems using three-phase systems. Accordingly, this research aims to demonstrate the impact of using PST with single and double transmission lines and to compare its performance under various operational modes.